2014
DOI: 10.2133/dmpk.dmpk-14-rg-010
|View full text |Cite
|
Sign up to set email alerts
|

Brivaracetam Single and Multiple Rising Oral Dose Study in Healthy Japanese Participants: Influence of CYP2C19 Genotype

Abstract: Brivaracetam is a high-affinity synaptic vesicle protein 2A ligand, in phase 3 clinical development for epilepsy. A phase 1, single-center, randomized, double-blind, placebo-controlled, single (2.5-100 mg) and multiple (2.5-50 mg twice daily) rising oral dose study (N01209) was conducted to assess the adverse event profile and pharmacokinetics of brivaracetam in healthy Japanese men, and the influence of the cytochrome P450 (CYP) 2C19 genotype. Plasma and urine were collected serially for analysis of brivarace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 19 publications
3
55
0
Order By: Relevance
“…Comparison of brivaracetam disposition in poor and extensive metabolizers of CYP2C19 indicated that brivaracetam is mainly hydroxylated by CYP2C19 but this pathway was deemed secondary to amide hydrolysis leading to the acid metabolite (Stockis et al, 2014). On the other hand, based on the results of an interaction study with omeprazole, it has been suggested that carbamazepine induces CYP3A4 but not, or to a lesser extent, CYP2C19 (Bertilsson et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison of brivaracetam disposition in poor and extensive metabolizers of CYP2C19 indicated that brivaracetam is mainly hydroxylated by CYP2C19 but this pathway was deemed secondary to amide hydrolysis leading to the acid metabolite (Stockis et al, 2014). On the other hand, based on the results of an interaction study with omeprazole, it has been suggested that carbamazepine induces CYP3A4 but not, or to a lesser extent, CYP2C19 (Bertilsson et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Brivaracetam is eliminated primarily by metabolism, with the major metabolic pathway involving hydrolysis of the acetamide group resulting in formation of an acid metabolite (brivaracetam-AC; 34.2% of a radiolabeled dose in urine) . A secondary pathway, mainly mediated by cytochrome P450 (CYP) 2C19 (Stockis et al, 2014), forms a hydroxy metabolite (brivaracetam-OH; 15.9% of dose in urine) . A combination of these two pathways leads to the formation of a hydroxyacid metabolite (15.2% of dose in urine) (Nicolas et al, 2012;Sargentini-Maier et al, 2008); only 8.6% of the dose is recovered as the unchanged compound in urine .…”
Section: Introductionmentioning
confidence: 99%
“…Brivaracetam is weakly bound to plasma proteins (~17.5%), and its half-life is about 8 h. Brivaracetam is renally excreted following extensive metabolism, primarily by hydrolysis and to a lesser extent by CYP-dependent hydroxylation Sargentini-Maier et al, 2008). The main isoenzyme responsible for hydroxylation was later shown to be CYP2C19 (Nicolas et al, 2012;Stockis et al, 2014b). Consistent with this, only 5-8% unchanged brivaracetam is excreted in urine (Rolan et al, 2008), along with pharmacologically inactive metabolites (von Rosenstiel et al, 2009).…”
Section: Pharmacokinetics and Metabolic Profilementioning
confidence: 99%
“…Pharmacokinetics of brivaracetam in healthy Japanese subjects genotyped for common mutations *2 and *3 of CYP2C19 (with no enzyme activity) showed that, although hydroxy metabolite formation was reduced 10-fold, there was only a 29% reduction in brivaracetam clearance which was considered to be of small clinical relevance. Therefore, dose adjustment is not required in CYP2C19 poor metabolizers (Stockis et al, 2014b).…”
Section: Pharmacokinetics and Metabolic Profilementioning
confidence: 99%
“…The major metabolic pathway involves the hydrolysis of the acetamide group, resulting in formation of an acid metabolite (BRV-AC; 34% of radiolabeled dose in urine) . Secondary pathways include CYP2C19-mediated hydroxylation of BRV to brivaracetam hydroxy metabolite (BRV-OH; 16% of dose in urine) Stockis et al, 2014) and CYP2C9-mediated hydroxylation of BRV-AC to the hydroxy acid metabolite (BRV-OHAC; Fig. 1; 15% of dose in urine Nicolas et al, 2012;Stockis et al, 2015).…”
Section: Brivaracetam [(2s)-2-[(4r)-2-oxo-4-propylpyrrolidinyl] Butanmentioning
confidence: 99%